Industrial Innovation for Open Strategic Autonomy - leaving no one and no place behind: Science-to-policy evidence from the 9th European Conference on Corporate R&D and Innovation - Sofia Amaral-Garcia; Hugo Confraria; Clemens Domnick; Fernando Hervás; Pietro Moncada Paternò Castello; Francesco Rentocchini; Elena Zaurino (European Commission, Joint Research Centre (JRC), 2023)
This document sets the scene and provides background information on 'Industrial Innovation for Open Strategic Autonomy", the main focus of the 9th edition of the European Conference on Corporate R&D and Innovation (CONCORDi 2023), as well as introduces scientific contributions that will be presented at the conference. It thus aims to stimulate fruitful discussions between academia, experts and policy-makers at the conference, identifying potential policy initiatives and areas where additional research and evidence are needed.
Keywords: 330; Innovation; EU-Forschungspolitik; EU-Industriepolitik; EU-Staaten